Matrix generalised Kummer relation - Díaz-García, José A.; Caro-Lopera, Francisco J. (South African Statistical Journal, 2015)
An extension of the well known matrix Kummer relation of Herz (1955) is proposed in this paper by assuming a general model which admits a Taylor expansion. Under certain conditions of the involved parameters, the addressed generalisation can be used for deriving efficiently computable matrix variate densities based on non Gaussian models, avoiding some open problems of the literature in the context of shape theory and other related fields.